A model of cardiac cellular electromechanics - Nickerson, D; Smith, N; Hunter, P (2001)
A coupled electromechanics model of a single cardiac cell is used to interpret a wide variety of experimental tests and is compared to a limited extent (since no other cardiac model dealing with the full range of mechanical tests is available) with other models of myofilament mechanics. We consider the passive elasticity of the cell, troponin-C-calcium binding kinetics, thin filament kinetics, the length dependence of steady-state tension, cross-bridge kinetics, and the coupling of mechanics to cell electrophysiology (the Noble 98 model) via the calcium transient.